Novel Bacillussubtilis IND19 cell factory for the simultaneous production of carboxy methyl cellulase and protease using cow dung substrate in solid-substrate fermentation. Issue 1 (December 2016) - Vijayaraghavan, Ponnuswamy; Arun, Arumugaperumal; Al-Dhabi, Naif; Vincent, Samuel; Arasu, Mariadhas; Choi, Ki
Abstract Background Hydrolytic enzymes, such as cellulases and proteases, have various applications, including bioethanol production, extraction of fruit and vegetable juice, detergent formulation, and leather processing. Solid-substrate fermentation has been an emerging method to utilize low-cost agricultural residues for the production of these enzymes. Although the production of carboxy methyl cellulase (CMCase) and protease in solid state fermentation (SSF) have been studied extensively, research investigating multienzyme production in a single fermentation process is limited. The production of multienzymes from a single fermentation system could reduce the overall production cost of enzymes. In order to achieve enhanced production of enzymes, the response surface methodology (RSM) was applied. Results Bacillus subtilis IND19 utilized cow dung substrates for the production of CMCase and protease. A central composite design and a RSM were used to determine the optimal concentrations of peptone, NaH2 PO4, and medium pH. Maximum productions of CMCase and protease were observed at 0.9 % peptone, 0.78 % NaH2 PO4, and medium pH of 8.41, and 1 % peptone, 0.72 % NaH2 PO4, and medium pH of 8.11, respectively. Under the optimized conditions, the experimental yield of CMCase and protease reached 473.01 and 4643 U/g, which were notably close to the predicted response (485.05 and 4710 U/g). These findings corresponded to an overall increase of 2.1- and 2.5-fold in CMCase and protease productions, respectively. Conclusions Utilization of cow dung for the production of enzymes is critical to producing multienzymes in a single fermentation step. Cow dung is available in large quantity throughout the year. This report is the first to describe simultaneous production of CMCase and protease using cow dung. This substrate could be directly used as the culture medium without any pretreatment for the production of these enzymes at an industrial scale.